Hydrogel composition for treating joint diseases

By developing a hydrogel composition based on anionic cyclodextrin polymer and chitosan, combined with wet granulation and acidification processes, the problem of difficult combination of pharmacological effects and lubrication effects in the prior art is solved, effective treatment of joint diseases is achieved, and long-term pain relief and lubrication effects are provided.

CN119698309APending Publication Date: 2025-03-25UNIV DE LILLE +5
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380057137.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-28
Filing Date
2023-07-28
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively combine pharmacological effects with lubricating effects (mucus supplementation) for the treatment of joint diseases, especially temporomandibular joint disorders (TMD) and osteoarthritis.

Method used

A hydrogel composition based on anionic cyclodextrin polymer and chitosan was developed, and the agent was added through wet granulation technology, and the hydrogel was formed through the acidification process to achieve a combination of pharmacological effects and lubricating effects.

Benefits of technology

The hydrogel composition can provide long-term pain relief and lubrication effects, avoid systemic side effects, and is suitable for intra-articular injection, which significantly improves joint health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005259485620000091
    Figure BDA0005259485620000091
  • Figure BDA0005259485620000101
    Figure BDA0005259485620000101
  • Figure BDA0005259485620000141
    Figure BDA0005259485620000141
Patent Text Reader

Abstract

The present disclosure relates to a hydrogel composition based on anionic cyclodextrin polymer and chitosan for use in the treatment of joint diseases. In particular, the hydrogels combine pharmacological effects, in particular analgesic effects, with mucus supplementation (lubrication effects).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hydrogel composition based on anionic cyclodextrin polymer and chitosan for treating joint diseases. Specifically, the present invention relates to a hydrogel composition based on cyclodextrin polymer and chitosan for treating joint diseases, which combines a pharmacological effect (especially analgesic effect) with a viscosupplementary effect (i.e., a lubricating effect). Background Art

[0002] Temporomandibular disorders (TMD), also known as temporomandibular joint dysfunction (TMJD), include conditions that affect the temporomandibular joint (the joint that connects the mandible to the skull). TMD is a myoarthropathy of the masticatory tissues that results in chronic painful symptoms and limited jaw movement. TMD is the leading cause of orofacial pain in the world, affecting 5% to 12% of the population in industrialized countries. According to the American Academy of Orofacial Pain, TDM includes a group of musculoskeletal and neuromuscular conditions involving the temporomandibular joint, the muscles of mastication, and all associated tissues. Among the painful symptoms, those that are more muscular (temporalis and / or masseter) can be distinguished from those that are more joint-specific. In this setting, the pain is usually caused by the anatomical substrate (e.g., intervertebral disc displacement that may or may not reduce, degenerative joint disease including osteoarthrosis and osteoarthritis).

[0003] The causes are varied and are often related to excessive mechanical stress, condylar region trauma, dental malocclusion, systemic diseases, hormones, and genetic factors (Tanaka E, Detamore MS, Mercuri LG. Degenerative disorders of the temporomandibular joint: etiology, diagnosis, and treatment. J Dent Res. avr 2008; 87(4): 296-307. Wang XD, Zhang JN, Gan YH, Zhou YH. Current understanding of pathogenesis and treatment of TMJ osteoarthritis. J Dent Res. may 2015; 94(5): 666-73). All of these causes lead to dysfunctional remodeling of joint components. In fact, the hypoxia caused by these factors leads to an upregulation of the production of vascular endothelial growth factor (VEGF) (Tanaka E, Detamore MS, Mercuri LG. Degenerative disorders of the temporomandibular joint: etiology, diagnosis, and treatment. J Dent Res. avr 2008; 87 (4): 296-307). VEGF increases the production of matrix metalloproteinases (MMPs) and reduces the production of tissue inhibitors of matrix metalloproteinases (TIMPs). This imbalance of effectors of extracellular matrix remodeling promotes bone and cartilage resorption. Hypoxia caused by overload also leads to the release of free radicals and proinflammatory cytokines (such as interleukin-1β (IL-1β); interleukin-6 (IL-6) and tumor necrosis factor-α (TNFα)). These cytokines regulate the production of hyaluronic acid (HA), and in the case of such high levels of proinflammatory cytokines, HA will degrade, resulting in a decrease in joint lubrication. The loss of synovial fluid and the resulting loss of viscosity impairs the nutritional support to the cartilage, leading to its gradual degeneration (Ernberg M. The role of molecular pain biomarkers in temporomandibular joint internal derangement. J Oral Rehabil. juin 2017; 44(6): 481-91).Similarly, IL-1β and TNF-α promote the production of MMPs and collagenases by synovial cells and articular chondrocytes (Tabeian H, Bakker AD, Betti BF, Lobbezoo F, Everts V, de Vries TJ. Cyclic Tensile Strain Reduces TNF-αInduced Expression of MMP-13 by Condylar Temporomandibular Joint Cells. J Cell Physiol. juin 2017; 232(6): 1287-94. Hutchinson NI, Lark MW, MacNaul KL, Harper C, Hoerrner LA, McDonnell J et al. In vivo expression of stromelysin in synovium and cartilage of rabbits injected intraarticularly with interleukin-1beta. Arthritis Rheum. oct 1992; 35(10): 1227-33. Kubota E, Imamura H, Kubota T, Shibata T, Murakami K. Interleukin 1beta and stromelysin (MMP3) activity of synovial fluid as possible markers of osteoarthritis in the temporomandibular joint. J Oral Maxillofac Surg. janv 1997; 55 (1): 20-7; discussion 27-28) and promotes the activation of cyclooxygenase-1 and 2 (COX-1 / 2), which enhances inflammation by increasing prostaglandin E2 (PGE2) levels (Satoh K, Ogura N, Akutsu M, Kuboyama N, Kuyama K, Yamamoto H et al., Expression of cyclooxygenase-1and-2in IL-1beta-induced synovitis of the temporomandibular joint. J Oral Pathol Med. 2009; 38(7): 584-90.Emshoff R, Puffer P, Rudisch A, Gassner R. Temporomandibular joint pain: relationship to internal derangement type, osteoarthrosis, and synovial fluid mediator level of tumor necrosis factor-alpha. Oral Surg Oral Med Oral Pathol Oral Radiol Endod. oct 2000; 90(4): 442-9). All these pathways play a role in the pathogenesis of TMJ osteoarthritis by promoting cartilage and bone degradation, reducing synovial fluid volume and producing chronic inflammation.

[0004] Symptoms are related to the ongoing inflammatory process and osteoarthropathy that constitute osteoarthritis. The main symptom is chronic oral-facial pain, which is a result of chronic synovitis, reactive muscle spasm and degenerative joint disease (Ahmad M, Schiffman EL. Temporomandibular Joint Disorders and Orofacial Pain. Dent Clin North Am. janv 2016; 60(1): 105-24). Other symptoms are often found in the setting of TMJOA: limited mandibular function: reduced mandibular mobility, limited speech and chewing, limited mouth opening, as well as pain on palpation and in the neck, and joint noises (Meloto CB, Slade GD, Lichtenwalter RN, Bair E, Rathnayaka N, Diatchenko L, et al., Clinical predictors of persistent temporomandibular disorder in people with first-onset temporomandibular disorder: A prospective case-control study. J Am Dent Assoc. juill 2019; 150(7):572-581. e10. Ohrbach R, Fillingim RB, Mulkey F, Gonzalez Y, Gordon S, Gremillion H, et al., Clinical findings and pain symptoms as potential risk factors for chronic TMD: descriptive data and empirically identified domains from the OPPERA case-control study. J Pain. nov. 2011;12(11Suppl):T27-45). Symptoms vary in intensity over time, alternating between periods of exacerbation, but may also become chronic.

[0005] Many treatment approaches have been considered in the complex management of these TMDs. Traditional non-invasive treatments combine sessions of physical therapy, occlusal therapy (usually requiring an occlusal release splint), and systemically administered symptomatic treatments (which combine analgesics and muscle relaxants). Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used by the oral route to reduce chronic inflammation, but they are associated with negative side effects due to systemic effects. For the articular type, where occlusal therapy has failed, treatment modalities are typically minimally invasive and include joint lavage (arthrocentesis) and / or intra-articular injections of various substances.

[0006] Hyaluronic acid (with known lubricating properties) as well as corticosteroids, morphine and its derivatives, ketamine or botulinum toxin (with analgesic properties) or even platelet-rich plasma (PRP) (which aids regeneration) are drug substances used in intra-articular injections with variable results.

[0007] Intra-articular injection of drug substances avoids their systemic effects (gastric and renal tolerance of non-steroidal anti-inflammatory drugs, metabolic problems of corticosteroids) (Al-Moraissi EA et al., J Cranio-Maxillo-fac Surg 2020;48(1):9-23). Supports based on biomaterials (nanoparticles, microparticles or hydrogels) have been proposed to administer drug substances in a controlled manner at the anatomical site of injection (Systematic review of studies on drug-delivery systems for management of temporomandibular-joint osteoarthritis. Barry F, Chai F, Chijcheapaza-Flores H, Garcia-Fernandez MJ, Blanchemain N, Nicot RJ Stomatol Oral Maxillofac Surg. 2021 Aug 13: S2468-7855(21)00163-4. doi: 10.1016 / j.jormas.2021.08.003. Online ahead of print). However, as described in the prior art, release must remain within an effective therapeutic window: the amount of active ingredient released must be sufficient to be effective over a long period of time, but not so large that it cannot prevent local cytotoxicity in the joint and damage to surrounding tissue (cartilage) (Cicognani M. et al., Pharmaceutics 2020; 12(7): 681. Deng Y et al., Sci Rep 2017; Kou L et al., Drug Deliv 2019; 26(1): 870-85).

[0008] Currently, there are no injectable substances available that combine the advantages of viscosupplementation (such as provided by hyaluronic acid) with an effective and safe pharmacological action. Currently used pharmaceutical substances lack long-term action (for nonsteroidal anti-inflammatory drugs) or have harmful local consequences by causing bone demineralization (for corticosteroids).

[0009] Therefore, there is still a need for an injectable composition for the treatment of TMD, and more generally for the treatment of joint diseases, which can combine pain relief with a lubricating effect (viscosupplementation). More specifically, there is still a need for an injectable composition for the treatment of TMD, and more generally for the treatment of joint diseases, which can combine a pharmacological action with a lubricating effect (viscosupplementation), combining this dual effect when it is desired or required. Summary of the invention

[0010] The present invention relates to a hydrogel composition comprising:

[0011] (a) A hydrogel made of a polymer network, the hydrogel comprising:

[0012] (i) chitosan;

[0013] (ii) anionic cyclodextrin polymers,

[0014] The anionic cyclodextrin polymer is a water-soluble anionic cyclodextrin polymer or a mixture of a water-soluble anionic cyclodextrin polymer and a water-insoluble anionic cyclodextrin polymer (CDPi), wherein the weight ratio of the water-soluble anionic cyclodextrin polymer to the water-insoluble cyclodextrin polymer is about 1:1;

[0015] wherein the ratio of the weight of chitosan to the total weight of the anionic cyclodextrin polymer is about 2:1; and

[0016] (b) optionally, a pharmaceutical agent, said pharmaceutical agent being incorporated into the polymer network,

[0017] Its use for treating joint diseases.

[0018] The present invention also relates to a method for preparing a hydrogel composition containing a pharmaceutical agent, the method comprising the following steps:

[0019] (i) providing a powder of a water-soluble anionic cyclodextrin polymer, a powder of a water-insoluble anionic cyclodextrin polymer where applicable, and chitosan;

[0020] (ii) adding the pharmaceutical agent to the water-soluble anionic cyclodextrin polymer powder or to a mixture of the water-soluble anionic cyclodextrin polymer powder and the water-insoluble anionic cyclodextrin polymer powder by wet granulation;

[0021] (iii) dry mixing the powder obtained in step (ii) with chitosan powder to form a powder mixture;

[0022] (iv) optionally sieving the powder mixture obtained in step (iii) or grinding and sieving together;

[0023] (v) suspending the powder mixture obtained in step (iv) in an aqueous medium having a pH capable of dissolving the anionic cyclodextrin polymer but not dissolving chitosan;

[0024] (vi) acidifying the suspension obtained from step (v) to form a hydrogel composition.

[0025] Other aspects of the invention are as disclosed herein and in the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : Inverted vial test was performed on CHT / PCDs / PCDi hydrogels and RP at 37°C, and the hydrogel formation was evaluated by flow time.

[0027] Figure 2 : The hydrogels were injected into PBS (80 rpm, at 37°C) to study the stability and cohesion of the hydrogels.

[0028] Figure 3 : Viscoelastic moduli were evaluated over the viscoelastic range of non-sterile hydrogels and RP: a) moduli G' and G" at 1% amplitude and 10 rad / s frequency; b) damping coefficient at 1% amplitude and 10 rad / s frequency.

[0029] Figure 4 : Viscosity curves of non-sterile hydrogel and RP at shear rates from 0 to 1000 s -1 .

[0030] Figure 5 : The recovery of non-sterile hydrogels and RP was evaluated by cyclic deformation method with shear amplitude cycles of γ0 = 1% in 180 s and γ1 = 500% in 120 s at 25°C.

[0031] Figure 6 : Viscoelastic moduli evaluation in the viscoelastic range of hydrogels with active molecules (CHT+PCDs / PCDi / NaNX): G' and G" moduli at 1% amplitude and 10 rad / sec frequency.

[0032] Figure 7 :Viscosity curves of hydrogels with active molecules (CHT+PCDs / PCDi / NaNX) with a shear rate scan range of 0 to 1000 s-1 .

[0033] Figure 8 Recovery (CHT+PCDs / PCDi / NaNX) was evaluated by cyclic deformation at 25°C with shear amplitude cycles of γ0=1% in 180 s and γ1=500% in 120 s.

[0034] Fig. 9 : Drug release was evaluated in a USP 1 dissolution apparatus at 37°C (PBS pH 7.4).

[0035] Fig.10 : The viability of fibroblast cell lines was obtained from the hydrogel CHT / PCDs / PCDi by extraction method.

[0036] Fig.11 : The torque was evaluated over 4 cycles (30 min, 25°C and 45 N) by using a PTFE-PTFE pin-on-disc system.

[0037] Fig.12 : Effect of sterilization on the viscoelastic moduli of hydrogels with and without active molecules: G' and G" moduli at 1% amplitude and 10 rad / sec frequency.

[0038] Fig.13 : Fibroblast cell line viability obtained from sterilized hydrogels by extraction method.

[0039] Fig.14 : Pain experienced by rats following injection of chemical agents into the TMJ. DETAILED DESCRIPTION

[0040] The present invention relates to a hydrogel composition as disclosed herein for the treatment of joint diseases. The hydrogel composition allows pain relief and lubrication effects (viscosupplementation) to be provided without the need for administration of a medicament. Thus, in some embodiments, the hydrogel composition does not contain any medicament, in particular does not contain a medicament as disclosed below.

[0041] In some embodiments, local release of the agent may be desired or required.The hydrogel composition then comprises the agent.

[0042] Examples of suitable joint diseases treatable as a result of the hydrogel composition of the present invention include, but are not limited to, osteoarthritis, osteoarthrosis (e.g., knee arthrosis), rheumatic diseases (e.g., rheumatoid arthritis or juvenile idiopathic arthritis), degenerative meniscus injury.

[0043] Osteoarthritis is one of the most common joint diseases and can affect all people (shoulders, knees, and temporomandibular joints). In some embodiments, the hydrogel composition is used to treat temporomandibular joint disease.

[0044] The pharmacological effect can be achieved by the release of the agent. Preferably, analgesia, i.e., pain relief, is achieved by releasing an analgesic from the hydrogel. Examples of suitable analgesics include, but are not limited to, opioid analgesics and nonsteroidal anti-inflammatory analgesics. Examples of opioid analgesics include codeine, oxycodone, and hydromorphone for ultimate severe pain. Examples of nonsteroidal anti-inflammatory agents include naproxen, ibuprofen, diflunisal, and ketorolac. In the case of rheumatic diseases such as rheumatoid arthritis or juvenile idiopathic arthritis, the composition may include an anti-TNFα drug.

[0045] In some embodiments, the present invention relates to a hydrogel composition as disclosed herein for treating bone and joint pain, in particular for treating temporomandibular joint pain. In some embodiments, the present invention relates to a hydrogel composition for postoperative pain control after arthroscopic or open joint surgery.

[0046] The composition of the present invention is based on hydrogel. Hydrogel is made of a polymer network expanded by water (particularly a large amount of water). In hydrogel, the bond between polymer chains can be permanent (covalent bond) or reversible (non-covalent bond, such as hydrogen bond, ionic bond, hydrophobic bond or dipole-dipole bond). Hydrogels with permanent bonds and hydrogels with reversible bonds are respectively called chemical hydrogels and physical hydrogels. The present invention relates to a composition based on physical hydrogel, which is cross-linked by ionic bonds between chitosan as a positive polyelectrolyte and cyclodextrin polymers as a negative polyelectrolyte. These ionic bonds are weak non-covalent interactions, which give these mixtures viscoelasticity, shear thickening and self-healing properties, thereby producing injectable properties.

[0047] It will be appreciated that the term "cyclodextrin polymer" as used herein refers to anionic cyclodextrin polymers, including when used in the expression "water-soluble cyclodextrin polymer" and "water-insoluble cyclodextrin polymer."

[0048] The hydrogel composition of the present invention has been found to be biocompatible, stable before and after sterilization, and exhibits properties that make it suitable for administration by injection (e.g., by syringe). The hydrogel composition of the present invention exhibits suitable viscoelastic properties (shear thinning and self-healing properties). The hydrogel composition fluidizes when exposed to mechanical shear stress, and recovers its viscoelastic properties when it returns to the linear viscoelastic region. Thus, in use, when the hydrogel composition is placed in the barrel of a syringe, it flows under the action of the shear stress applied by the plunger, and recovers its cohesive state when the stress is released, i.e., when it has been injected into the treatment area. The viscosity of the hydrogel composition is neither too low nor too high, so that it can effectively lubricate the joint without disturbing the joint. The hydrogel composition of the composition was found to exhibit similar properties to hyaluronic acid. The lubrication properties of are equivalent to the lubrication properties of.

[0049] The hydrogel composition of the present invention has suitable tribological properties. It is strong enough to resist the forces of the joint for at least two to three weeks.

[0050] The hydrogel compositions of the present invention have been found to provide pain relief even in the absence of a pharmaceutical agent.

[0051] It has also been found that the hydrogel compositions of the present invention are capable of appropriately local release of medicaments for extended periods of time. Combined medicaments may also be released. Local administration avoids undesirable effects that may be encountered when the medicament is administered systemically. The slow and extended release provided by the hydrogel compositions of the present invention allows for the delivery of an effective amount of the medicament while preventing any toxicity (the amount of the medicament released is below its toxicity threshold). Suitably, the hydrogel compositions of the present invention are capable of relieving pain over a period of two to three weeks.

[0052] This valuable combination of properties is achieved due to the specific formulation of the hydrogel composition.

[0053] Due to all these properties, the hydrogel compositions of the present invention are particularly suitable for the treatment of joint diseases, especially when a combination of pharmacological action and viscosupplementation is desired or required.

[0054] The hydrogel composition of the present invention comprises:

[0055] (a) A hydrogel made of a polymer network, the hydrogel comprising:

[0056] (i) chitosan;

[0057] (ii) a cyclodextrin polymer, wherein the cyclodextrin polymer is a water-soluble cyclodextrin polymer or a mixture of a water-soluble cyclodextrin polymer and a water-insoluble cyclodextrin polymer, wherein the weight ratio of the water-soluble cyclodextrin polymer to the weight of the water-insoluble cyclodextrin polymer is about 1:1;

[0058] wherein the ratio of the weight of chitosan to the total weight of the cyclodextrin polymer is about 2:1;

[0059] (b) optionally, a pharmaceutical agent, preferably an analgesic agent, which is incorporated into the polymer network.

[0060] The hydrogel composition according to the invention is based on a physical hydrogel formed by the interaction between two appositively charged polymers: chitosan (cationic polymer) and cyclodextrin polymers (anionic polymers). Chitosan usually carries protonated amino groups on its glucosamine repeating units, and / or anionic cyclodextrin polymers usually carry carboxylate groups on their polycarboxylic acid crosslinks.

[0061] The term "about" in the context of the present invention means that the value involved may be 10% lower or higher than the indicated value, in particular 5% lower or higher, especially 1% lower or higher. It includes the indicated value and values ​​that are 10% lower or higher (in particular 5% lower or higher, in particular 1% lower or higher) than the indicated value. As an example, when a range is said to vary from about X to about Y, it includes the range from X to Y and optionally includes values ​​that are 10% lower (in particular 5% lower, in particular 1% lower) than X and values ​​that are 10% higher (in particular 5% higher, in particular 1% higher) than Y.

[0062] Chitosan

[0063] Chitosan is a linear polymer that assumes an extended coil conformation in solution, which ensures the macromolecular structure of the hydrogel and imparts the desired rheological properties to it.

[0064] Chitosan is a biocompatible and biodegradable cationic polymer. It is a linear polysaccharide composed of randomly distributed β-1,4-linked D-glucosamine (deacetylated units) and N-acetyl-D-glucosamine (acetylated units). Chitosan can be made by deacetylation of chitin, a structural component of the exoskeleton of crustaceans, or can be directly extracted from fungi.

[0065] Chitosan can be characterized by its degree of deacetylation, which represents the percentage of deacetylated glucosamine units in its macromolecular chain. Chitosan suitable for the present invention generally has a degree of deacetylation ranging from 60% to 95%, preferably greater than or equal to 70% and preferably less than 90% or less than or equal to 76%.

[0066] Chitosan is commercially available in the form of powder or fragments of varying particle sizes.

[0067] Chitosan is insoluble in aqueous media with a pH greater than or equal to 4, greater than or equal to 4.5, and especially greater than or equal to 5. In contrast, chitosan dissolves in acidic aqueous media with a pH below 4. When the aqueous solution is sufficiently acidic, the amine functional group -NH2 of the D-glucosamine repeating unit of chitosan is protonated to an ammonium functional group -NH3 + . It should be noted that at a pH of less than or equal to 5 and greater than or equal to 4, the amine functional groups of chitosan will be partially protonated, but the amount of protonation is not sufficient to dissolve the chitosan. The degree of protonation to be achieved in order to obtain solubilization also depends on the molecular weight and the degree of deacetylation of the chitosan: if the degree of deacetylation is low, a higher proportion of the amine functional groups must be protonated compared to a high degree of deacetylation due to the hydrophobicity of the acetyl-D-glucosamine repeating unit. Chitosan with a degree of deacetylation (DDA) of 70% contains 4.04 mmol of amino groups per gram. For chitosans with a DDA of 80% and 90%, respectively, the amino content increases to 4.73 mmol / g and 5.45 mmol / g.

[0068] The molecular weight of chitosan may be in the range of 200 to 300 kDa. Chitosan suitable for use in the present invention typically has a molecular weight of 256 kDa.

[0069] In some embodiments, the hydrogel comprises 1 to 3 wt% chitosan relative to the total weight of the hydrogel, preferably the hydrogel comprises about 2 wt% chitosan relative to the total weight of the hydrogel.

[0070] Cyclodextrin polymers

[0071] The cyclodextrin polymer used in the present invention acts as a physical crosslinker in the hydrogel composition by establishing ionic bonds with the chitosan chain network. Such ionic bonds stabilize the hydrogel structure and impart elastic properties to it at rest, and the ionic bonds can be broken when strain is applied, thereby providing shear thinning properties, and reformed instantly at rest, thereby providing self-healing properties. The cyclodextrin polymer ensures the cohesive and viscoelastic properties of the hydrogel, so that the hydrogel cannot spontaneously dissolve and migrate in physiological media. The cyclodextrin polymer also forms inclusion complexes with the pharmaceutical agent, so that the pharmaceutical agent can be slowly locally released.

[0072] Cyclodextrin polymers are polymers derived from cyclodextrins. Cyclodextrins are cyclic oligomers composed of 6, 7 or 8 α-(1,4)-linked pyranose glucose units, known as [α]-cyclodextrin, [β]-cyclodextrin and [γ]-cyclodextrin, respectively. The structure of cyclodextrins can be compared to a truncated cone, with a hydrophilic exterior and a hydrophobic interior that forms a cavity capable of reversibly forming inclusion complexes with molecules, preferably hydrophobic molecules.

[0073] The cyclodextrin polymer of the present invention is generally obtained by polycondensation of natural cyclodextrin (α, β, γ cyclodextrin) or cyclodextrin derivatives (hydroxypropyl, methyl cyclodextrin) and polycarboxylic acid (such as citric acid or 1,2,3,4-butanetetracarboxylic acid) through crosslinking.

[0074] The known cyclodextrin polymers obtained by the above-mentioned routes may be soluble or insoluble in water, depending on their structure.

[0075] The cyclodextrin polymers suitable for use in the present invention include water-soluble cyclodextrin polymers and water-insoluble cyclodextrin polymers.

[0076] As disclosed in EP 1 165 621, water-soluble anionic cyclodextrin polymers and water-insoluble anionic cyclodextrin polymers can be prepared by polycondensation between (poly) carboxylic acids and natural cyclodextrins (α, β, γ) or their derivatives (methyl, hydroxypropyl cyclodextrin). Depending on the extension of the polycondensation reaction, the polymer obtained is soluble in water or insoluble in water. The soluble form of these cyclodextrin polymers presents a hyperbranched structure, forming a spherical substance of about 50 nanometers. The insoluble form is the result of an extended degree of polymerization, which causes a cross-linked structure, resulting in water-insoluble properties. However, this insoluble form is highly hydrophilic and easily swells in water, with a swelling rate of up to 450% to 500% (this means that the insoluble cyclodextrin polymer can absorb up to five times its own weight of water). The chemical structure of the soluble form and the insoluble form is the same. The difference lies in the expansion of the cross-linking rate that affects its molar mass. The cyclodextrin polymers as used in the present invention, in particular the cyclodextrin polymers obtained by the process disclosed in EP 1 165 621, are characterized by a high cyclodextrin content (e.g. 40 to 65 wt. % relative to the total weight of the polymer) and a high amount of anionic carboxyl functional groups (e.g. 3 to 5 mmol / g cyclodextrin polymer).

[0077] The cyclodextrin polymer used in the present invention, in particular the cyclodextrin polymer obtained by the method, has a molar mass of about 15000 to 30000 g / mol, in particular 20000 to 30000 g / mol, preferably 20000 to 25000 g / mol. Thus, even in the absence of high molar mass polymers such as hyaluronic acid, the hydrogel of the present invention is able to provide a lubricating effect (mucous replenishment). The molar mass of the polymer as disclosed herein refers to the number average molar mass calculated by size exclusion chromatography (SEC) or gel permeation chromatography (GPC).

[0078] Soluble cyclodextrin polymers and insoluble cyclodextrin polymers are generally obtained according to the method disclosed in EP 1 165 621. A mixture produced by a polycondensation reaction between cyclodextrin and polycarboxylic acid in a solid state is suspended in water and then separated by filtration on a sintered glass funnel. The insoluble portion is washed with water and dried, while the filtrate is dialyzed and then freeze-dried to obtain a soluble portion as a powder. When preparing the hydrogel composition according to the present invention, the soluble form of the powder and the insoluble form of the powder are weighed and mixed in a predetermined ratio.

[0079] The cyclodextrin polymers suitable for use in the present invention contain in particular 3.5 to 4.5 mmoles / g of carboxylic acid functional groups, typically about 4 mmoles / g of carboxylic acid functional groups. The number of moles of carboxyl functional groups per gram of cyclodextrin polymer can be measured by acid-base titration in the presence of a chromogenic indicator. The measurement method comprises dissolving a predetermined amount of cyclodextrin polymer in a given volume of water in the presence of a chromogenic indicator such as phenolphthalein (a few drops) and then gradually adding (dropwise) a 0.1 mol / l sodium hydroxide solution to the solution under stirring (e.g. using a magnetic rod), in particular using a graduated tube, until the solution containing the chromogenic indicator changes color. The number of moles of sodium hydroxide added then corresponds to the number of moles of carboxylic acid functional groups neutralized.

[0080] In some embodiments, the polymer network of the hydrogel comprises only water-soluble cyclodextrin polymers as cyclodextrin polymers.

[0081] In some embodiments, the polymer network of the hydrogel comprises a mixture of a water-soluble cyclodextrin polymer and a water-insoluble cyclodextrin polymer as the cyclodextrin polymer, and the ratio of the weight of the water-soluble cyclodextrin polymer to the weight of the water-insoluble cyclodextrin polymer is 1:1.

[0082] In some embodiments, the hydrogel comprises 1 to 3 wt% of the cyclodextrin polymer relative to the total weight of the hydrogel, preferably the hydrogel comprises 1 wt% of the cyclodextrin polymer relative to the total weight of the hydrogel.

[0083] In some embodiments, the hydrogel contains up to 3 weight percent of water-soluble cyclodextrin polymers and no water-insoluble cyclodextrin polymers relative to the total weight of the hydrogel, typically contains 1 to 3 weight percent of water-soluble cyclodextrin polymers and no water-insoluble cyclodextrin polymers, relative to the total weight of the hydrogel, preferably contains 1 weight percent of water-soluble cyclodextrin polymers and no water-insoluble cyclodextrin polymers, relative to the total weight of the hydrogel.

[0084] In some embodiments, the hydrogel comprises 0.5 wt % of a water-soluble cyclodextrin polymer and 0.5 wt % of a water-insoluble cyclodextrin polymer relative to the total weight of the hydrogel.

[0085] In some embodiments, the hydrogel comprises 1 wt% to 3 wt% chitosan, 1 wt% to 3 wt% cyclodextrin polymer (soluble and / or insoluble portion of the cyclodextrin polymer), and 94 wt% to 98 wt% water (typically water containing 1 wt% acid).

[0086] Hydrogel composition

[0087] In some embodiments, the hydrogel composition does not contain a pharmaceutical agent.In some embodiments, the hydrogel composition consists of a hydrogel as disclosed above.

[0088] In some embodiments, the hydrogel composition comprises 95% to 99.9% by weight of hydrogel (preferably 99% to 99.5% by weight of hydrogel) and 0.1% to 5% by weight of the pharmaceutical agent (preferably 0.1% to 1% or 0.5% to 1% by weight of the pharmaceutical agent) relative to the total weight of the composition. Preferably, the pharmaceutical agent is an analgesic.

[0089] In some embodiments, the hydrogel composition comprises 1 wt % of the pharmaceutical agent, preferably 1 wt % of the analgesic agent, relative to the total weight of the composition.

[0090] The pH of the hydrogel composition is generally in the range of 3 to 5, preferably 3.1 to 3.5 or 4.2 to 4.5.

[0091] Examples of suitable compositions include the following:

[0092]

[0093]

[0094] Preparation of hydrogel compositions

[0095] The hydrogel composition containing a pharmaceutical agent can be suitably prepared by adding the pharmaceutical agent when preparing the hydrogel.

[0096] Hydrogel can be suitably prepared according to the method disclosed in WO WO2017 / 001808. In the disclosed method, cyclodextrin polymers (soluble cyclodextrin polymers and insoluble cyclodextrin polymers) and chitosan are provided in powder form. As used herein, the term "powder" refers to a solid material reduced to small particles at ambient temperature. Powders of cyclodextrin polymers (mixed insoluble forms and soluble forms, or only soluble forms) and chitosan are dry mixed to form a powder mixture. The obtained powder mixture is suspended in an aqueous medium, and then the resulting suspension is acidified under strong stirring to form a bulk viscoelastic hydrogel (bulk viscoelastic hydrogel), wherein the aqueous medium has a pH that enables the soluble cyclodextrin polymer to dissolve without dissolving chitosan (also without dissolving insoluble cyclodextrin polymers), such as pH greater than or equal to 4, pH greater than or equal to 4.5, or even greater than or equal to 5.

[0097] Based on this method, the hydrogel composition of the present invention can be prepared as described in detail below. The hydrogel composition can be prepared at room temperature.

[0098] Cyclodextrin polymers (soluble cyclodextrin polymers and insoluble cyclodextrin polymers) and chitosan are provided as powders. The powders may be sterilized prior to use.

[0099] Powder preparation

[0100] Chitosan and cyclodextrin polymers can be used as raw powders (i.e., uncalibrated particles). The cyclodextrin polymer powder and / or chitosan powder can be sieved before use. It can be suitably sieved through a sieve in which the mesh has a certain size, the size being less than or equal to 500 μm, for example less than or equal to 300 μm, or even less than or equal to 200 μm, particularly less than or equal to 150 μm, more particularly less than or equal to 125 μm. Chitosan powder and cyclodextrin polymer powder can be sieved by means of a vibrating screen (e.g., a vibrating screen sold by Fritsch).

[0101] In some embodiments, the cyclodextrin polymer powder and / or chitosan powder may be ground prior to sieving, for example with the aid of a Pulverisette sold by Fritsch and provided with a 120 μm screen. Machine. Grinding can reduce the size of solid particles and form smaller fragments. Control of the particle size of chitosan and insoluble cyclodextrin polymer can be important in the preparation of hydrogels. In fact, small particles are more easily suspended in water, allowing chitosan to dissolve quickly after acidification of the suspension. These parameters are not only important for the gel formation time, but also for the uniformity of the bulk hydrogel (no lumps in the hydrogel).

[0102] In some embodiments, the water-soluble cyclodextrin polymer powder and, when present, the water-insoluble cyclodextrin polymer powder are ground in a mortar and sieved through a 125 μm sieve. The chitosan is ground separately before sieving, for example with the aid of a Pulverisette sold by Fritsch and provided with a 120 μm sieve. The obtained chitosan powder was then sieved again using a 125 μm sieve.

[0103] In some embodiments, cyclodextrin polymer powder and / or chitosan powder are ground to obtain particles with an average size below 125 microns. The size distribution of particles of chitosan powder and / or cyclodextrin polymer powder or a mixture of chitosan powder and cyclodextrin polymer powder can be measured using a Mastersizer S (Malvern Instruments, Orsay, France) with a 300 mm lens. The sample is dispersed with 4 bar of compressed air in a dry state.

[0104] Addition of medicine

[0105] Addition of the agent may be performed by any suitable method.

[0106] The medicament is usually added to the cyclodextrin polymer powder by wet granulation. Since the medicament can react with the chitosan amino group, this process can prevent any interaction that may affect the formation and stability of the hydrogel. The medicament can be added to the water-soluble cyclodextrin polymer powder or the mixture of the water-soluble cyclodextrin polymer powder and the water-insoluble cyclodextrin polymer powder that may have been ground and / or sieved before use. The medicament and the cyclodextrin polymer powder are provided in the ratio described above.

[0107] Wet granulation can be performed by any method known in the art. For example, the cyclodextrin polymer powder and the medicament can be placed in a mortar. Water is then added (e.g., in a ratio of 4:1 (w / w)), and the resulting mixture is stirred. The mixture is then placed in an oven at 60°C for 1 hour and 30 minutes. The resulting powder can then be ground and sieved to obtain particles with a size below 125 microns.

[0108] The cyclodextrin polymer powder containing the pharmaceutical agent and the chitosan powder are then dry mixed. A mixer mill may be suitably used for dry mixing.

[0109] In some embodiments, the resulting mixture may be sieved or ground and sieved together.Sieving may be performed as disclosed above.

[0110] In some embodiments, the cyclodextrin polymer powder and / or chitosan powder containing the pharmaceutical agent can be co-grinded, for example, they can be co-grinded manually in a mortar or co-grinded with a Mixer Mill MM400 sold by Restch (Steinbach, Germany). The term "co-grinding" refers to the simultaneous grinding of at least two different powders. It has been observed that co-grinding and / or mixing after grinding can reduce the size of the solid particles of the powders and can also provide sufficient mixing between the powders (thereby providing better contact surface area between the cyclodextrin polymer and the chitosan, thereby facilitating electrostatic interactions). Grinding promotes the uniformity of the aqueous dispersion formed with these powders in the next step of the method. The reproducibility of hydrogel formation is also improved, and the uniformity of the hydrogel is improved, and no visible agglomerates appear.

[0111] Preparation and acidification of suspension to form hydrogel composition

[0112] After dry mixing and optional sieving or grinding and sieving, the obtained mixture of cyclodextrin polymer powder and chitosan powder containing the pharmaceutical agent (if present) is then suspended in an aqueous medium having a pH at which the cyclodextrin polymer is dissolved but chitosan is not dissolved. The suspension is preferably stirred. The pH of the aqueous medium is appropriately in the range of 5 to 6, preferably 5.5 to 6. The pH values ​​shown herein are measured using a pH meter at ambient temperature (i.e., 20° C. to 25° C.). The expression "insoluble chitosan" as used herein means that in the aqueous medium, the chitosan has no protonated amine functional groups or the number of protonated amine functional groups of the chitosan is insufficient to cause the chitosan powder to dissolve. The aqueous medium is preferably water (e.g., distilled water or ultrapure water). Typically, at least 0.5% by volume or even at least 1% by volume of an acid relative to the total volume of the aqueous medium can be added to the aqueous medium.

[0113] The resulting suspension is then acidified to form a hydrogel composition. After the addition of the acid, the pH of the suspension is reduced, in particular to a pH lower than or equal to 5, more particularly lower than or equal to 3, in particular lower than or equal to 4, which allows the chitosan to be solubilized by protonation of its amines to ammonium functional groups. The chitosan macromolecules unfold under the intramolecular electrostatic repulsion between the ammonium groups formed, and a "critical" concentration C* (usually expressed in g / cm 3 The critical concentration C* corresponds to a concentration above which the polymer coils overlap. At the same time, ionic bonds are formed between the ammonium groups of the chitosan and the anionic functional groups of the cyclodextrin polymers. Then, when the amine functional groups are protonated, the pH of the hydrogel rises to a stabilization, preferably a pH greater than or equal to 4, even more preferably a pH greater than or equal to 4.5, in particular a pH greater than or equal to 5.

[0114] Suitable acids that can be added to the suspension to form the hydrogel composition include, but are not limited to, acetic acid (particularly glacial acetic acid), formic acid, tartaric acid, salicylic acid, glutamic acid, propionic acid, hydrochloric acid, citric acid, lactic acid, and mixtures thereof. Preferred suitable acids include acetic acid, hydrochloric acid, lactic acid, and mixtures thereof. More preferred suitable acids include lactic acid and hydrochloric acid, particularly lactic acid.

[0115] It has been observed that the firmness and stability of the injected hydrogel composition are better in the case of these acids, in particular lactic acid. Moreover, very dilute hydrochloric acid solutions and lactic acid solutions have the advantage of being odorless compared to acetic acid. The added lactic acid may be an aqueous solution comprising at least 85% by weight of pure lactic acid relative to the volume of the aqueous solution.

[0116] Typically, the acidification is performed by adding an aqueous composition comprising at least 1 wt % lactic acid. In addition, the acidification step needs to be accompanied by vigorous stirring. Shear forces promote rapid dissolution of chitosan and formation of hydrogel.

[0117] The present invention also relates to a method for providing a hydrogel composition as described herein, comprising the following steps:

[0118] (i) providing a water-soluble cyclodextrin polymer powder, a water-insoluble cyclodextrin polymer powder where applicable, and a chitosan powder;

[0119] (ii) adding the pharmaceutical agent to the water-soluble cyclodextrin polymer powder or to a mixture of the water-soluble cyclodextrin polymer powder and the water-insoluble cyclodextrin polymer powder by wet granulation;

[0120] (iii) dry mixing the powder obtained in step (ii) with chitosan powder to form a powder mixture;

[0121] (iv) optionally sieving the powder mixture obtained in step (iii) or grinding and sieving together;

[0122] (v) suspending the powder mixture obtained in step (iv) in an aqueous medium having a pH capable of dissolving the water-soluble cyclodextrin polymer but not dissolving chitosan, such as a pH greater than or equal to 4, a pH greater than or equal to 4.5, or even a pH greater than or equal to 5;

[0123] (vi) acidifying the suspension obtained from step (v) to form a hydrogel composition.

[0124] The steps of the method are disclosed in detail above.

[0125] In other words, the present invention also relates to a hydrogel composition which is easily obtainable by a process comprising the following steps:

[0126] (i) providing a water-soluble cyclodextrin polymer powder, a water-insoluble cyclodextrin polymer powder where applicable, and a chitosan powder;

[0127] (ii) adding the pharmaceutical agent to the water-soluble cyclodextrin polymer powder or to a mixture of the water-soluble cyclodextrin polymer powder and the water-insoluble cyclodextrin polymer powder by wet granulation;

[0128] (iii) dry mixing the powder obtained in step (ii) with chitosan powder to form a powder mixture;

[0129] (iv) optionally sieving the powder mixture obtained in step (iii) or grinding and sieving together;

[0130] (v) suspending the powder mixture obtained in step (iv) in an aqueous medium having a pH capable of dissolving the water-soluble cyclodextrin polymer but not dissolving chitosan, such as a pH greater than or equal to 4, a pH greater than or equal to 4.5, or even a pH greater than or equal to 5;

[0131] (vi) acidifying the suspension obtained from step (v) to form a hydrogel composition.

[0132] Step (vi) is usually carried out under stirring at a high shear rate.

[0133] The disclosed method can be implemented with an apparatus comprising a first syringe receiving chitosan, cyclodextrin polymer powder and a medicament and a second syringe receiving a predetermined volume of an acidified aqueous medium, the apparatus comprising a device for fluidly connecting the first syringe and the second syringe in such a manner that the acidified aqueous mixture is combined with a mixture comprising chitosan, cyclodextrin polymer powder and the medicament. The device for fluidly connecting can be optionally detached from the first syringe and the second syringe. The first syringe and the second syringe can be fluidly connected at their injection ends via a device for fluidly connecting (e.g., Luer Lock), the device allowing the acidified aqueous medium to be introduced into the first syringe with the help of the plunger of the second syringe and vice versa via the plunger of the first syringe. The plunger is actuated multiple times (about 50 to 70 repetitions) until a hydrogel is formed; the shear force generated promotes the dissolution of the chitosan powder and the ionic interaction with the anionic cyclodextrin polymer, thereby facilitating the formation of a stable and firm hydrogel.

[0134] Application of hydrogel compositions

[0135] The hydrogel composition can be suitably administered by injection, in particular by intra-articular injection. The injection can be performed using a device comprising the hydrogel. The device is preferably a syringe comprising at least one container filled with the hydrogel composition, typically a predetermined volume of the hydrogel composition.

[0136] In some embodiments, the device for administering the hydrogel composition comprises a first syringe containing a mixture comprising chitosan, cyclodextrin polymer powder, and, if present, a pharmaceutical agent, preferably a suspension as described herein, containing chitosan, cyclodextrin polymer powder, and, if present, a pharmaceutical agent, and a second syringe containing a predetermined volume of an acidified aqueous medium, the device comprising a device for fluidly connecting the first syringe and the second syringe in such a manner that the acidified aqueous medium is combined with the mixture comprising chitosan, cyclodextrin polymer powder, and, if present, a pharmaceutical agent. When the hydrogel composition is formed as disclosed above, the syringe containing the hydrogel composition can be equipped with a needle, and the hydrogel composition can then be injected.

[0137] The present invention also relates to a method for treating joint diseases, particularly when a combination of pharmacological action and viscosupplementation is desired or required, comprising administering to an individual in need thereof an effective dose of a hydrogel composition as disclosed herein. Administration of the hydrogel composition is generally performed by injection, particularly by intra-articular injection.

[0138] The effective dosage of the hydrogel composition varies according to many parameters, such as the body weight, age, sex, state of advancement of the disease to be treated and the sensitivity of the individual to be treated.

[0139] The invention also relates to a hydrogel composition for use in the preparation of a medicament for the treatment of joint diseases, in particular when a combination of pharmacological action and viscosupplementation is desired or required.

[0140] Embodiments of the present invention will now be described by way of the following examples, which are provided for illustrative purposes only and are not intended to limit the scope of the present disclosure.

[0141] Example

[0142] abbreviation

[0143] CHT Chitosan

[0144] PCDs water-soluble anionic cyclodextrin polymer

[0145] PCDi Water-insoluble anionic cyclodextrin polymer

[0146] NaNX Naproxen Sodium

[0147] βCDβ-cyclodextrin

[0148] Example 1: Stability of hydrogel

[0149] The hydrogels were prepared according to the method disclosed in WO2017 / 001808. The cohesiveness of the following formulations was evaluated (Table 1).

[0150] Table 1: CHT:PCDs:PCDi formulations

[0151]

[0152] After the hydrogel was prepared, the cohesion of the hydrogel was evaluated by injecting it into a vial and inverting it. 1 mL of the hydrogel was injected into the vial at 37°C and the resistance to flow was visually evaluated over time.

[0153] Use a method called A hyaluronic acid-based product (RP) was used as a control and was tested simultaneously ( Figure 1 ).

[0154] All CHT / PCDs / PCDi formulations tested formed hydrogels.

[0155] The RP flow resistance was lower (less than 8 seconds) compared to the one of the CHT / PCDs / PCDi formulation.

[0156] Variable cohesion was observed between samples. The 2:1:0 formulation showed high resistance to flow (>2h) compared to the 1.5:1.5:0 formulation (2h). Addition of PCDi resulted in a decrease in resistance to flow, reflecting the weaker cohesion of the hydrogels (1.5:0.75:0.75 and 2:0.5:0.5).

[0157] The hydrogel was then injected into a buffer solution (buffered phosphate saline PBS, pH 7.4, 80 rpm, 37°C) using an 18G needle to test the cohesion of the hydrogel in a medium simulating physiological pH. Since RP is a hyaluronic acid-based solution, it does not form a viscous product after injection (it forms a solution with PBS, the results are not presented).

[0158] The results are presented in Figure 2 Linear structures were observed for all samples. However, stronger cohesion was observed for the 2:1:0 and 2:0.5:0.5 hydrogels over 24 hours compared to the 1.5:0.75:0.75 and 2:0.5:0.5 hydrogels. More specifically, the 2:0.5:0.5 hydrogel exhibited the highest stability.

[0159] The 1.5:1.5:0 and 1.5:0.75:0.75 hydrogels showed weak cohesion over 24 hours. In fact, formulation 1.5:1.5:0 lost its structure after 1 hour due to shrinkage, while formulation 1.5:0.75:0.75 partially lost its linear structure and formed lumps.

[0160] In summary, it was observed that the hydrogels according to the invention (i.e., 2:1:0 and 2:0.5:0.5 hydrogels) have stronger cohesiveness. The hydrogels according to the invention are stable.

[0161] Although the 2:1:0 formulation has a higher flow resistance, the addition of PCDi improves the structural stability of the 2:0.5:0.5 formulation.

[0162] Example 2: Viscoelasticity of Hydrogels

[0163] Rheological measurements of G' and G" (Pa) were performed using a rheometer in the linear viscoelastic region (γ = 1%, frequency = 10 rad / sec, 37 °C). The results are presented in Table 2 below and Figure 3 in.

[0164] As shown in Table 2, the G' of the CHT / PCDs / PCDi hydrogel is higher than G" (G' > G"), indicating the formation of a viscoelastic solid.

[0165] It can be observed that compared with (referred to as R.P.), the CHT / PCDs / PCDi hydrogel has superior viscoelastic properties. In fact, R.P. has properties corresponding to a viscoelastic solid, but the difference between G' and G" is small, and it can be concluded that it exhibits weaker cohesiveness.

[0166] Tanδ (Table 2), also known as the damping coefficient, is a parameter that helps to distinguish the internal energy (or intermolecular forces) of a viscoelastic solid. In rheology, the value of Tanδ is calculated based on the G" / G' ratio; thus, tan d > 100:1 = 100 is considered an ideal viscous liquid; 0.01 < tan d < 100 is considered viscoelastic properties; tan d < 1:100 = 0.01 is considered an ideal elastic solid.

[0167] In the case of the CHT / PCDs / PCDi formulation, it was observed that the value of tanδ (<0.82) is lower compared to R.P. (0.92). This demonstrates that the hydrogel has higher solid elastic properties. Regarding the CHT / PCDs formulation, a similar tanδ value (0.56) was observed, and the same is true for the formulation containing CHT / PCDs / PCDi ( Figure 3 ).

[0168] Table 2: Values of Moduli G' and G" and Tanδ

[0169]

[0170] In summary, the CHT:PCDs / PCDi hydrogel composition in Table 2 behaves as a solid viscoelastic material, while RP behaves as a viscous liquid.

[0171] Example 3: Injectability of hydrogels (viscosity versus shear rate study)

[0172] The injectability of the hydrogels was investigated by rheological measurements of viscosity evolution relative to shear rate sweeps (25 °C). CHT / PCDs / PCDi hydrogels as well as RP were tested to understand the effect of the addition of PCDs to the formulation. RP had a lower flow resistance (at 1000 s -1 s at 1000 s), while the resistance of CHT / PCDs / PCDi hydrogel was slightly higher (0.16 Pa.s at 1000 s -1 0.47 to 0.49 Pa / s) Figure 4 ; Table 3). It can be concluded that CHT / PCDs / PCDi and RP are non-Newtonian and have shear-thinning properties.

[0173] These properties demonstrate the injectability of the hydrogel.

[0174] Table 3: At 0s -1 and 1000s -1 Viscosity value under (Pa.s)

[0175]

[0176] Example 4: Self-healing of hydrogels (G' modulus recovery relative to deformation)

[0177] The self-healing property is the ability of some hydrogels to reorganize their structure after internal bonds have been broken under deformation caused by mechanical stress. The recovery of hydrogels under different shear stresses was evaluated to determine the recovery rate of the hydrogels. Weak (γ = 1%) and strong (γ = 500%) stress cycles were applied to all samples at 25°C.

[0178] Figure 5 The G' and G" moduli of CHT / PCDs / PCDi hydrogels and RP according to the applied 1% and 500% shear amplitude cycles are shown. At low shear amplitudes, G' is superior to G", and the gel has solid viscoelastic properties. The impact of high stress triggers the G' modulus to decrease below the G" value, which shows the flow property. G' recovery is then observed upon returning to low shear amplitude. The G' recovery rate of CHT / PCDs / PCDi and RP is above 90%. The explanation is that at low shear amplitudes, chitosan interacts with PCDs and PCDi through ionic bonds (they form polyelectrolyte complexes). At high shear amplitudes, the ionic interactions are destroyed, both polymers regain fluidity and the system flows (G">G'). Within a short time after the low shear amplitude is then applied again, the ionic bonds are immediately regenerated and the initial parameters are restored.

[0179] Therefore, the CHT / PCDs / PCDi formulation can be considered as a self-healing hydrogel.

[0180] Example 5: Hydrogel Formulation with Pharmaceutical Agents

[0181] Preparation of hydrogel compositions containing pharmaceutical agents

[0182] NaNX was added to the formulation at a concentration of 1% w / w by PCDs / PCDi / NaNX wet granulation as described previously.

[0183] Rheological evaluation of hydrogel compositions containing pharmaceutical agents

[0184] The hydrogels were evaluated as disclosed above.

[0185] G' and G" Assessment over Time

[0186] Rheological evaluation was performed to assess any changes after the addition of NaNX.

[0187] Figure 6 The formation of hydrogels in both cases is shown (G'>G"). Indeed, the inclusion of NaNX triggers an increase in the G' modulus. Values ​​of 230 Pa and 55 Pa for G' and G" moduli were observed in formulation 2+1:0:1 and 130 Pa and 50 Pa, respectively, in formulation 2+0.5:0.5:1 (Table 4).

[0188] Tan δ values ​​were also compared, with formulations with the agent (<0.39) forming stronger hydrogels compared to formulations without the agent (0.50-0.82).

[0189] In conclusion, stronger hydrogels were formed after wet granulation between PCD and NaNX. This test demonstrated that the addition of NaNX allowed the viscoelastic properties of CHT+PDCs:PCDi hydrogels to be maintained.

[0190] Table 4: Evaluation test values ​​of G' and G"

[0191]

[0192] Study of Viscosity vs. Shear Rate

[0193] Figure 7 The viscosity of the hydrogel composition containing NaNX is shown. -1 The viscosity increased significantly at 415 and 268 (Table 5). The hydrogel without NaNX showed a four-fold increase relative to the initial value.

[0194] The results showed that the addition of NaNX maintained the non-Newtonian and shear-thinning properties of CHT+PDCs:PCDi hydrogels. As mentioned above, the shear-thinning property is related to the injectability of the hydrogel.

[0195] Table 5: At 0s -1 and 1000s -1 Viscosity value under (Pa.s)

[0196]

[0197] recover

[0198] The test was performed using the same experimental parameters as previously described. Similar properties were observed, with approximately 90% G' recovery obtained. As previously described, this test shows that the polymer network structure is lost at high shear amplitudes, while new ionic bonds are reorganized upon return to low stress ( Figure 8 ).

[0199] In vitro release studies

[0200] Release studies were performed to evaluate the kinetics of NaNX release. A 0.8 g amount of the hydrogel composition (see Table 6) was injected into a 1 kDa regenerated cellulose dialysis membrane ( Spectrum Laboratories, Inc. The samples were then tested in 500 mL of USP 1 dissolution system (Agilent, France) in phosphate buffered saline (PBS) at 37° C. All tests were performed in triplicate.

[0201] All samples were analyzed by ultra-high performance liquid chromatography coupled to a diode array detector (Shimadzu Nexera-i LC-2040 3D plus). The mobile phase consisted of a mixture of acetonitrile / orthophosphoric acid pH 2.25 (65:35) injected at a flow rate of 1 mL / min into a C18 column (4*250 mm) stabilized at 25°C. The injection volume was fixed at 20 μL and the detection wavelength was 225 nm. The retention time was determined to be 4.2 minutes to calculate the area under the curve (AUC).

[0202] Table 6: Weight % of Naproxen Released

[0203]

[0204] First, similar release profiles were observed for both cases; in fact, the release plateau was reached after 36 hours. Some minor differences were also observed between the two formulations, with the 2+1:0:1 hydrogel releasing more drug (86.0 wt %), while the 2+0.5:0.5:1 hydrogel released 78.1 wt % ( Fig. 9 ).

[0205] Example 6: Evaluation of cytotoxicity

[0206] According to the ISO 10993-5 standard, the cytotoxicity of hydrogel formulations 2:0.5:0.5 and 2:1:0 was evaluated by the extraction method (indirect contact) using the NIH / 3T3 fibroblast cell line (see Table 1). The hydrogel was pretreated in MEM-α medium for 2 hours at 37°C and 80rpm. The culture medium was removed and a concentration of 200mg hydrogel / 1mL culture medium was added. On the other hand, NIH3T3 cells were seeded in a cell culture plate to form a cell blanket. The number of cells seeded in 100μL of complete culture medium was 4×103 cells / well, and incubated for 24 hours at 37°C and 5% CO2. After incubation, each extraction medium (n=2) was sterilized using a 0.22μm filter. Then, the cell layer culture medium was replaced with 100μL of sterile extraction medium. The cells were incubated for another 24 hours at 37°C and 5% CO2. Finally, by using Cell viability was assessed by fluorescence assay using the ELISA kit (Uptima, Interchim, France). Fluorescence readings were measured at 530 nm as excitation wavelength and 590 nm as emission wavelength. Cell metabolic activity was expressed as a percentage of fluorescence intensity relative to the control value ( Fig.10 ).

[0207] Fig.10 The percentage of cell survival after exposure to the hydrogel with culture medium is shown. High cell viability was observed for both formulations compared to the control. This test demonstrates the safety of this hydrogel for human administration.

[0208] Example 7: Tribological study

[0209] Tribological studies were performed on 2:0.5:0.5 hydrogels (see Table 1) using a Tribo-Rheometer MCR 301 (Anton Paar, Les Ulis, France) connected to a T-PID 44 friction unit and a SCFE7 measurement attachment. The lubricating activity of the hydrogel and RP was determined using 3 pins and PTFE disk attachments. A deflection angle of 50mrad, an angular frequency of 6rad / s, and a normal force of 45N were applied. Before starting each cycle, pre-stabilization was performed to decompress the system. The protocol included a deflection angle of 0.014mrad, an angular frequency of 1rad / s, and a normal force of 15N for 5 minutes.

[0210] The torque was measured for 30 minutes over 4 cycles. At the same time, sterilized samples of the formulation were tested and the results are shown in Fig.11 middle.

[0211] The hydrogel 2:0.5:0.5 was also compared to a physiological solution (NaCl 0.9%) as a negative control. In the first cycle, the negative control and the non-sterilized sample had similar properties. Next, the negative control tended to increase over time, while the formulation 2:0.5:0.5 decreased over time, demonstrating the lubricating activity of the formulation 2:0.5:0.5.

[0212] Example 8: Sterilization of hydrogel

[0213] CHT and PCD powders were sterilized using ethylene oxide (EtO) sterilization and gamma irradiation, respectively. The sterilization procedure was performed according to ISO 11135 and ISO 11137 standards for sterilization of health products. EtO sterilization consists of 3 parts: prepackaging, sterilization (exposure to EtO for 3 hours), and aeration. EtO gas was eliminated by using air exchange in the sterilization chamber to remove remaining EtO particles.

[0214] Gamma irradiation sterilization was performed using a cobalt-60 (60Co) irradiation source at a dose of 40 kGy.

[0215] The effect of sterilization on the hydrogels was performed for the formulations CHT / PCDs / PCDi 2:0.5:0.5 and CHT+PCDs / PCDi / NaNX 2+0.5:0.5:1. Studies evaluating viscoelastic properties (G' and G") and cytocompatibility (only for formulations without NaNX) were performed.

[0216] The results obtained are shown in Fig.12 and Table 7. The viscoelastic properties were evaluated as described previously ( Fig.12 , Table 7), the results showed that the elastic modulus was higher than the viscous modulus, which confirmed the formation of hydrogel (G'>G").

[0217] Table 7: Values ​​of elastic modulus and viscous modulus (Pa) before and after sterilization

[0218]

[0219] Then, cytocompatibility studies were performed according to ISO 10993-5 as described previously. No differences in cell viability were observed after sterilization ( Fig.13 ). In fact, a cell viability value of 100% was obtained (exceeding the cell viability before sterilization by 93.8%), demonstrating its cytocompatibility.

[0220] Example 9: Preclinical studies of hydrogels

[0221] A total of 20 male Wistar rats (6 weeks old) were used in each group, with an average body weight of 221.6 g (range 193 to 267 g). Animals were raised in a temperature-controlled room (22 + / - 1 ° C) with a 12-12 hour light-dark cycle. After receipt, each animal was placed in a separate cage and food and water were provided ad libitum. Under general anesthesia, a left temporomandibular joint (TMJ) injection of 0.5 mg sodium iodoacetate (MIA, Sigma, Saint Louis, USA) dissolved in 50 μL of saline solution was performed to induce TMJ osteoarthritis. Using anatomical landmarks, the solution was injected into the upper compartment of the left TMJ with a 26-gauge needle. 2 days after the MIA injection, the same injection technique was used for both joints (2: 0.5: 0.5 and RP) for the therapeutic agent.

[0222] Fig.14 :Before injection of therapeutic agent (-2, 0 days) and after injection 2, 7, 14, 21 and 30 days, the pain experienced by rats after injection of chemical agent in TMJ was measured by Von Frey tactile meter. In short, hard plastic tip was used on the left side to stimulate the midpoint of connection between the eyes and ears of rat head and face. During the experimental operation, the mechanical stimulation intensity increased, and accordingly, the behavior of rats was observed at the same time. When the reaction such as rubbing the mouth or scratching the head or the head retreated was observed, the stimulation intensity (g) was recorded as the head retreat threshold (HWT), which is defined as the minimum pressure that causes nociception on TMJ. Afterwards, the rats were allowed to rest for a few minutes, and then the same operation was applied on the right side. HWT was calculated as the mean value of each joint of all test rats / groups.

[0223] Although HWT on the (left) side decreased significantly 2 days after MIA injection, HWT recovered to original levels from D14 after 2:0.5:0.5 hydrogel injection, emphasizing the lubricating effect of the hydrogel. Compared with RP, HWT was significantly higher in the hydrogel group from D14 to D30.

Claims

1. A hydrogel composition comprising: (a) A hydrogel made of a polymer network, the hydrogel comprising: (i) chitosan; (ii) an anionic cyclodextrin polymer, which is a water-soluble anionic cyclodextrin polymer or a mixture of a water-soluble anionic cyclodextrin polymer and a water-insoluble anionic cyclodextrin polymer (CDPi), wherein the weight ratio of the water-soluble anionic cyclodextrin polymer to the water-insoluble anionic cyclodextrin polymer is about 1:1; wherein the ratio of the weight of chitosan to the total weight of the anionic cyclodextrin polymer is about 2:1; and (b) optionally a pharmaceutical agent incorporated into the polymer network, The hydrogel composition is used for treating joint diseases.

2. The hydrogel composition for use according to claim 1, wherein The agent is present and is an analgesic.

3. The hydrogel composition for use according to claim 2, wherein The analgesic is selected from opioid analgesics such as codeine, oxycodone and hydromorphone and nonsteroidal anti-inflammatory agents such as naproxen, ibuprofen, diflunisal and ketorolac.

4. A hydrogel composition for use according to any one of the preceding claims, wherein The joint diseases are osteoarthritis, osteoarthritis, rheumatic diseases and degenerative meniscus injury.

5. A hydrogel composition for use according to any one of the preceding claims, wherein: The hydrogel composition is administered by intra-articular injection.

6. A hydrogel composition for use according to any one of the preceding claims, wherein: The hydrogel contains 2 wt% of chitosan and 1 wt% of a water-soluble anionic cyclodextrin polymer relative to the total weight of the hydrogel.

7. A hydrogel composition for use according to any one of the preceding claims, wherein The hydrogel comprises 2 wt% of chitosan, 0.5 wt% of a water-soluble anionic cyclodextrin polymer, and 0.5 wt% of a water-insoluble anionic cyclodextrin polymer, relative to the total weight of the hydrogel.

8. A hydrogel composition for use according to any one of the preceding claims, wherein The hydrogel composition comprises 0.1 wt % to 5 wt %, preferably 0.1 wt % to 1 wt % of the pharmaceutical agent relative to the total weight of the hydrogel composition.

9. A method for preparing a hydrogel composition as claimed in any one of the preceding claims, said hydrogel composition comprising a pharmaceutical agent, said method comprising the steps of: (i) providing a powder of a water-soluble anionic cyclodextrin polymer, a powder of a water-insoluble anionic cyclodextrin polymer where applicable, and chitosan; (ii) adding the pharmaceutical agent to the water-soluble anionic cyclodextrin polymer powder or to a mixture of the water-soluble anionic cyclodextrin polymer powder and the water-insoluble anionic cyclodextrin polymer powder by wet granulation; (iii) dry mixing the powder obtained in step (ii) with chitosan powder to form a powder mixture; (iv) optionally sieving the powder mixture obtained in step (iii) or grinding and sieving together; (v) suspending the powder mixture obtained in step (iv) in an aqueous medium having a pH capable of dissolving the anionic cyclodextrin polymer but not dissolving chitosan; (vi) acidifying the suspension obtained from step (v) to form a hydrogel composition.

10. The method according to claim 9, wherein: Step (vi) is performed by adding an acid selected from acetic acid, formic acid, tartaric acid, salicylic acid, glutamic acid, propionic acid, hydrochloric acid, citric acid, lactic acid and mixtures thereof, preferably the acid is lactic acid or hydrochloric acid.

Citation Information

Patent Citations

  • Cyclodextrin polymers and / or cyclodextrin derivatives with complexing properties and ion-exchange properties and method for the production thereof

    EP1165621A1

  • Method for the production of hydrogel comprising chitosan and negatively charged polyelectrolytes, and cellular, porous material resulting from said hydrogel

    WO2017001808A1